Keeping Your Temple Clean: Health Promotion and Religious Function - Kelly, Michael P. (Journal of religion and health, 1999)
This article describes various approaches for partnering health-promotion interventions with parish functions. Specifically, nutrition, physical activity, bereavement, social, and intellectual health are addressed. By augmenting parish function to promote health, the faith group enables and encourages parishioners to adopt health-enhancing action. Finally, it explores the responsibility of a faith group to care for the health of members.